Auto Insurance Reform for Canada’s Tort Provinces - Kleffner, Anne E.; Nielson, Norma L. (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2004)
Due to its mandatory nature, and because a majority of the population drives, a cost-effective and efficient system of automobile insurance is in the interest of all parties involved. Although a tort system for compensating automobile accident victims works reasonably well for that relatively small number of claimants with serious losses, it does not work very well for the higher volume of relatively minor accidents. In this paper, we suggest means by which Canadian jurisdictions operating a system of tort liability can control costs and improve compensation for accident victims. Suggested reforms focus on improving coordination between public and private-pay aspects of health care; setting first-party benefits at a level which reduces the transaction costs without increasing aggregate costs; reducing or limiting access to payments for compensation for non-economic losses for non-permanent injuries; encouraging an efficient mechanism for dispute resolution; and developing a pricing system that is perceived to be fair by insureds while also providing incentives for safe driving.